1996
DOI: 10.1001/archinte.1996.00440080101012
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Spectrum of Jin Bu Huan Toxicity

Abstract: Herbal medications and other nontraditional medical therapies are becoming increasingly popular in the United States. We describe three children and three adults in whom severe toxic effects developed after ingestion of a Chinese herbal medication, jin bu huan, which is sold as Jin Bu Huan Anodyne Tablets. Jin bu huan produced distinct clinical syndromes after acute ingestion in children and long-term use in adults. A single, acute ingestion in children rapidly produced life-threatening neurologic and cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…[table/ fig-2]: Herbal Medicines which are associated with toxicity [18][19][20][21][22][23][24][25] …”
Section: Pulmonary Infiltrates With Esinophilicmentioning
confidence: 99%
“…[table/ fig-2]: Herbal Medicines which are associated with toxicity [18][19][20][21][22][23][24][25] …”
Section: Pulmonary Infiltrates With Esinophilicmentioning
confidence: 99%
“…Retrospective assessment of unintentional reexposure tests is cumbersome, because clinical conditions are variable, as shown in the present report (Tables 1 and 4) [1][2][3][4][5] and in previous case analyses [14,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] . Specific criteria for reexposure tests are available since 1988 (Table 3) [31] and have been incorporated in the CIOMS scale (Table 4) [16,32,34] following successful use for validation purposes [33] .…”
Section: Discussionmentioning
confidence: 77%
“…Data problems of reexposure cases are not confined to Herbalife products (Table 4) but represent a general problem extending to liver injury by all herbal drugs, dietary supplements and herbal products [14,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] . Analysis of 30 cases within the last three decades claiming a positive reexposure test revealed that in many cases detailed descriptions of the reexposure test and actual ALT values were lacking.…”
Section: Items For Hepatocellular Type Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…For reexposure assessments of the cholestatic (± hepatocellular) type of liver injury, ALT has to be replaced by ALP. Criteria for positive reexposure tests are included in the updated CIOMS scale (Tables 5 and 6) and were not previously applied in cases with reported positive reexposure tests [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]59,91] . When these cases were submitted to retrospective analysis using the reexposure test criteria, a positive reexposure test could be confirmed in only 13/30 cases, the test was negative in 5/30 cases and uninterpretable in 12/30 cases [91] .…”
Section: Cioms Scalementioning
confidence: 99%